Effectiveness of a Fully Automated Internet-Based Smoking Cessation Program: A Randomized Controlled Trial (STAMP). Issue 2 (23rd January 2018) - Nguyen Thanh, Viet; Guignard, Romain; Lancrenon, Sylvie; Bertrand, Camille; Delva, Catherine; Berlin, Ivan; Pasquereau, Anne; Arwidson, Pierre
Abstract: Introduction: The Internet offers an interesting alternative to face-to-face and telephone-based support for smoking cessation. This study was designed to assess the effectiveness of a personalized and automated Internet-based program. Methods: French current adult smokers willing to quit within 2 weeks were recruited for a randomized controlled trial. The intervention consisted of an automated program of 45 e-mails (" e-coaching ") sent over a 3-month period. The control group received a PDF version of a booklet on smoking cessation. Self-reported 7-day point prevalence smoking abstinence was measured at 6 months (primary outcome), at 3 and 12 months of follow-up (secondary outcomes). Results: 2478 smokers were randomized (1242 for e-coaching, 1236 for the booklet). Cessation rate in the intention-to-treat population was not significantly different between the two groups at 6 and 12 months, but was higher in the e-coaching group at 3 months than in the control group (27.5% vs. 23.5%, p = .02, odds ratio [ OR ] = 1.24, confidence interval [CI] = [1.03–1.49]). After adjustment for baseline conditions, the effect of the intervention in the per-protocol (PP) sample was significant at 3 months (adjusted odds ratio [ aOR ] = 1.72 [1.31–2.28], p < .001, N = 1042) and at 6 months ( aOR = 1.27 [1.00–1.60], p = .05, N = 1082). GLM repeated measure analyses showed significant group by time interaction in the intent-to-treat and a significant group effect in the PP population. Conclusions: Analyzed intention-to-treat, e-coaching was superior to a booklet at 3 months (end of intervention) but no more superior at 6 and 12 months follow-up. Among those who actually followed the program, the effectiveness is also observed 3 months after the intervention is stopped. Implications: Analyzed intention-to-treat, our French tailored and personalized Internet-based cessation program was superior to a smoking cessation booklet at 3 months (end of intervention) but no more superior at 6 months follow-up. Among those who actually followed the program (PP population), the effectiveness is observed in the short-term but also 3 months after the intervention is stopped.